Mirabegron: pharmacoeconomic aspects of the use of the drug for the treatment of overactive bladder syndrome - O. I. Ivakhnenko; E. V. Derkach; V. S. Krysanova; A. D. Ermolaeva; K. A. Kokushkin (Izdatelstvo OKI, 2022)
According to the International Continence Society (ICS), symptoms of overactive bladder (OAB) are present in 17 % of the adult population of Europe. The prevalence of overactive bladder in Russia is unknown but is considered comparable to that in European countries. According to Russian guidelines, patients with OAB could be treated with antimuscarinics or beta 3-agonists. The results of a meta-analysis by Wang J et al. (2018) showed comparable efficacy and safety of mirabegron and solifenacin. At the same time, according to Chapple CR et al. (2017) and Yeowell G et al. (2018) the use of mirabegron is associated with greater adherence to therapy and longer average drug use before the need to change therapy compared to antimuscarinics. From an economic point of view, greater adherence to drug therapy is associated with lower costs per patient with OAB per year and mirabegron have demonstrated to be cost-eff ective in comparison to solifenacin. The results of the analysis of the structure and volume of providing various types of medical care to patients with OAB in the Moscow region demonstrate the need to expand approaches to providing drug care to this group of patients. Currently, the majority of costs related to patients with OAB are associated with surgical treatment, which indicates the opportunity to expand the possibilities of drug therapy, including within the framework of preferential drug provision.